2018
DOI: 10.31744/einstein_journal/2019ao4410
|View full text |Cite
|
Sign up to set email alerts
|

Quando a cor ajuda

Abstract: ObjectiveTo reduce the inappropriate identification of eye drops, through the use of different colors.MethodsA group of 34 healthy volunteers was presented to two groups of four eye drops each. All eye drops were placed in identical, unlabelled vials. In one group, all four eye drops were transparent. In the other group, each had a different color. A number was assigned to each eye drop, and the volunteer was asked to identify it by color. We measured the correct index in the identification of the eye drops of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One study tested the impact of color differences to help in identifying eye drops and showed that there was a 64% improvement in correct identification of medications based only on analysis of the color of the substance of eye drops from identical bottles. 32 In the present study, we detail the idealization and development of multisensory sleeves and evaluation of the acceptance of this new method to help reduce the risk of confusion between eye medications. Misuse of ocular medications is a subject that has only been poorly explored so far, but it is of great importance and needs to be addressed so that more solutions are proposed for increasing the safety of users.…”
Section: Introductionmentioning
confidence: 99%
“…One study tested the impact of color differences to help in identifying eye drops and showed that there was a 64% improvement in correct identification of medications based only on analysis of the color of the substance of eye drops from identical bottles. 32 In the present study, we detail the idealization and development of multisensory sleeves and evaluation of the acceptance of this new method to help reduce the risk of confusion between eye medications. Misuse of ocular medications is a subject that has only been poorly explored so far, but it is of great importance and needs to be addressed so that more solutions are proposed for increasing the safety of users.…”
Section: Introductionmentioning
confidence: 99%